UNDERSTANDING THE PRACTICE OF ETHICAL LEADERSHIP AMONG SCHOOL PRINCIPALS: EVIDENCE FROM MALAYSIA - Siva Vikaraman , Sharmini; Norhaini Mansor, Azlin; Izham Mohd Hamzah, Mohd; Isa Medina, Nitce; Gurusamy, Vasanthan (International Journal of Psychosocial Rehabilitation, 2020)
Ethical leadership is a type of value-based leadership that highly aids in balancing the principal’s role as a manager and leader in schools. Studies have shown the impact of practicing ethical leadership towards building trust, positive workplace behavior, increasing innovative workplace mindset, and organizational performance. The emerging leadership style has found strong roots in the international platforms but not in the Malaysian local school leadership interest. 3 secondary school principals were selected for this study based on the ethical leadership level as perceived by their teachers from a previous study by the researcher. A previous study shows that principals have a high to moderately high level of ethical leadership practice in schools. This case study caters to findings on the understanding and practices of ethical leadership style among the principals as perceived by the principals themselves. The study also explored the seven dimensions of ethical leadership as being practiced among the principals. A semi-structured interview was conducted to collect relevant data. The interview was transcribed and thematically analyzed. The principals sharing revealed that they lacked an understanding of ethical leadership style but practiced several dimensions of ethical leadership in their daily school administration tasks. The findings suggest that ethical leadership has ample room to be integrated into current school leadership practices and be made understood of its impact on improving teacher work performance.